Ofloxacin-ornidazole fixed-dose combination medication-induced pancreatitis with positive rechallenge - Nikhil Bush; Vishal Sharma; K Chandrahasan; Amol N Patil (Journal of Family Medicine and Primary Care, 2020)
Although ofloxacin-ornidazole fixed-dose combination (FDC) is a rampantly used antibiotic combination for mixed-infection diarrhea in India, the adverse drug reaction (ADR) associated with these FDCs remains underreported. Herein, the authors present a case report of a definitive ofloxacin-ornidazole FDC-induced pancreatitis. The nonalcoholic adult male patient showed a sharp piercing epigastric pain flowing to the back, gradually rising in severity, which started after taking ofloxacin-ornidazole FDC tablet over the counter. Serum lipase concentration measured in the emergency room was 635 units per liter (normal range- 13–60 units/L) and serum amylase was 377 units/L (normal range- 30–110 units/L). Ultrasonography and an axial computed tomography of the abdomen confirmed the diagnosis of acute pancreatitis. Ofloxacin-ornidazole FDC tablet was stopped immediately. Past treatment records confirmed accidental rechallenge. In conclusion, this is a first case report of ofloxacin-ornidazole FDC-induced pancreatitis.